Domestic Violence against Women and COVID-19 - Constantina Zamba; Marilena Mousoulidou; Andri Christodoulou (Encyclopedia, 2022)
Domestic violence against women is defined as harmful behavior that occurs within a home and it involves aggressive and violent conduct towards women. Since the outbreak of the COVID-19 pandemic, and following the restrictions imposed to combat the pandemic (lockdowns, staying at home, isolation), domestic violence against women has increased worldwide. The current entry presents existing knowledge and discusses issues important for public awareness.